Institutional Repository as a Catalyst for Enhanced University Visibility: The case of Obafemi Awolowo University - Olakunle Adeyemo, Oladapo; Jamogha, Ejiro (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2021)
Purpose: Nigeria has a great number of universities and research institutes who produces high volume of scholarly work which is mostly not visible to information users because of the absence, reluctance, and value placed on institutional repository. This paper seeks to bring to the forefront the benefits and opportunities IR offers scholars, researchers, institutions and the nation at large. The paper also examines in depth the purpose and importance of creating a university publication unit in the library, stating the different types of materials that can be acquired and organized in the section. Issues facing the digitization of publications and research outputs in Obafemi Awolowo University were addressed so that university libraries can learn and excel in establishing their own university publication unit and institutional repository. Recommendations for librarians, university community, management and the government were stated. Approach: The paper reviewed literature to examine the importance of having institutional repository and publication unit in the library. The paper also revealed extensively different information resources accessible for researchers and information users. Findings: The paper showed that research output from Institutional repository have a key role in information gatherings which is essential in decision making and policy making for national development. Originality/Value: The paper provided valuable insight into the benefits of awareness programs in achieving a successful and beneficial institutional repository.